Regulation of glycolytic metabolism by autophagy in liver cancer involves selective autophagic degradation of HK2 (hexokinase 2). Issue 4 (3rd April 2018) - Jiao, Lin; Zhang, Hai-Liang; Li, Dan-Dan; Yang, Ke-Li; Tang, Jun; Li, Xuan; Ji, Jiao; Yu, Yan; Wu, Rui-Yan; Ravichandran, Senthilkumar; Liu, Jian-Jun; Feng, Gong-Kan; et al.
ABSTRACT: Impaired macroautophagy/autophagy and high levels of glycolysis are prevalent in liver cancer. However, it remains unknown whether there is a regulatory relationship between autophagy and glycolytic metabolism. In this study, by utilizing cancer cells with basal or impaired autophagic flux, we demonstrated that glycolytic activity is negatively correlated with autophagy level. The autophagic degradation of HK2 (hexokinase 2), a crucial glycolytic enzyme catalyzing the conversion of glucose to glucose-6-phosphate, was found to be involved in the regulation of glycolysis by autophagy. The Lys63-linked ubiquitination of HK2 catalyzed by the E3 ligase TRAF6 was critical for the subsequent recognition of HK2 by the autophagy receptor protein SQSTM1/p62 for the process of selective autophagic degradation. In a tissue microarray of human liver cancer, the combination of high HK2 expression and high SQSTM1 expression was shown to have biological and prognostic significance. Furthermore, 3-BrPA, a pyruvate analog targeting HK2, significantly decreased the growth of autophagy-impaired tumors in vitro and in vivo (p < 0.05). By demonstrating the regulation of glycolysis by autophagy through the TRAF6- and SQSTM1-mediated ubiquitination system, our study may open an avenue for developing a glycolysis-targeting therapeutic intervention for treatment of autophagy-impaired liver cancer.